The Utilization of Augmented Reality at the Space Shape of the Flat Side Material in the Eight Grade Studet of SMP/MTs - Tarto Sanusi (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2021)
Media or teaching materials are things that are owned by a teacher for the learning process. A teacher must be creative in designing and utilizing technological media in mathematics learning, smartphones are tools for learning based on augmented reality to make virtual thinking easier in learning mathematics, especially flat-sided building materials to provide virtual-based simulations for student thinking. The benefits of using augmented reality-based media 1) students' critical thinking and interested in learning 2) Helping students with learning activities 3) can be used anywhere It only requires batteries 4) minimal RAM to operate does not require expensive costs 5) practical and efficient in this study using descriptive qualitative research method, research place at SMP Negeri One Atap Kandang Kapongan Situbondo for grade VIII students. Constraints in utilizing augmented reality learning media 1). Not accustomed to inspiring 2) students who do not have Android-based smartphones 3) using smart phones in schools is not for learning. Keywords: augmented reality , Build Flat Side Space